HIF3A DNA methylation, obesity and weight gain, and breast cancer risk among Mexican American women. Issue 6 (November 2020) - Shen, Jie; Song, Renduo; Ye, Yuanqing; Wu, Xifeng; Chow, Wong-Ho; Zhao, Hua
Abstract: Objective: In previous epigenome-wide association studies, Hypoxia inducible Factor 3 Alpha Subunit ( HIF3A ) DNA methylation has been reported to be associated with body mass index (BMI) and weight change. However, none of these studies have included Mexican Americans. Methods: In the current study, we assessed levels of HIF3A methylation in 927 Mexican American women identified from Mano-A-Mano, the Mexican American Cohort study. Results: Significantly higher methylation levels at three CpG sites (position 46801557, 46801642, and 46801699) were observed in obese women compared to non-obese women (P < 0.05). Furthermore, we found that elevated methylation levels at those three CpG sites were associated with significant weight gain (P < 0.05), defined as an increase in BMI by at least one category between the baseline and the follow-up, with a median follow-up time of 39 months. Then, using pre-diagnostic blood DNA samples, we found increased DNA methylation at CpG 46801642 to be associated with a 1.35-fold increased risk of breast cancer (Hazard Ratio (HR) = 1.35, 95% Confidence Interval (CI): 1.02, 3.01), with a median follow-up time of 127 months. Using the Cancer Genome Atlas (TCGA) data, we further found that levels of HIF3A were significantly higher-methylated and down-regulated in breast tumor than in normal tissues (P < 1 × 10 12 for both). Conclusion: Thus, our results provide evidence to support the role of HIF3A in obesity, weight gain, and the development of breast cancer.